A Behavior Genetic Analysis of Trait Emotional Intelligence and Alexithymia: A Replication. (9th January 2013) - Baughman, Holly M.; Schermer, Julie Aitken; Veselka, Livia; Harris, Juliette; Vernon, Philip A.
Abstract : This replication study examines relations between alexithymia and trait emotional intelligence (trait EI) at the phenotypic, genetic, and environmental levels. A sample of 1, 444 same-sex twin pairs (850 MZ pairs and 594 DZ pairs) completed the Toronto Alexithymia Scale-20. A subset of 494 same-sex twin pairs (287 MZ pairs and 207 DZ pairs) had earlier completed the Trait Emotional Intelligence Questionnaire. Individual differences in alexithymia were attributable to genetic, non-shared environmental, and shared environmental factors. All but one of the facets of alexithymia were negatively and significantly correlated with the factors of trait EI, and these phenotypic correlations were entirely attributable to correlated genetic and correlated non-shared environmental factors. These bivariate results provide a valuable replication of those of Baughman et al. ( Twin Research and Human Genetics, Vol. 14, 2011, pp. 539–543), which was conducted with substantially smaller samples of twins.